Filling Disks of Hayman Type of Meromorphic Functions - Nan Wu; Zuxing Xuan (Journal of Function Spaces)
We obtain the existence of the filling disks with respect to Hayman directions. We prove that, under the condition limsupr→∞⁡(Tr,f/log⁡r3)=∞, there exists a sequence of filling disks of Hayman type, and these filling disks can determine a Hayman direction. Every meromorphic function of positive and finite order ρ has a sequence of filling disks of Hayman type, which can also determine a Hayman direction of order ρ.